New science program makes use of facilities and expertise at the first Bio-Sciences Hub in Africa - Persley, Gabrielle J. (International Livestock Research Institute, 2011)
Gabrielle Persley gave an emphasis on the choice of the location for the headquarters of Bio-innovate depended on access to the best bioscience facilities and expertise in the region. The BecA Hub, at the ILRI Nairobi campus, provides a vibrant biosciences research platform for advanced research into crops and livestock.